Serum Uric Acid Levels Are Associated With Macula Microvasculature Changes In Hypertensive White Matter Hyperintensity Patients - Wei, Ruili; Xie, Jianyang; Meng, Fangxia; He, Fangping; Liu, Jiang; Zhao, Yitian; Liang, Hui (Current Neurovascular Research, 2023)
Purpose: To characterize the macula microvasculature using fractal dimension (FD) in hypertensive white matter hyperintensity (WMH) participants and explore the association between the microvascular changes and serum uric acid levels. Methods: Thirty-eight WMH participants were dementia and stroke-free, and 37 healthy controls were enrolled. Optical coherence tomographic angiography (OCTA) was used to image the superficial vascular complex (SVC), deep vascular complex (DVC), and inner vascular complex (IVC) in a 2.5-mm diameter concentric circle (excluding the foveal avascular zone FAZ). A commercial algorithm was used to quantify the complexity and density of the three capillary layers by fractal analysis. Results: WMH participants showed significantly lower FD value in the SVC (P = 0.002), DVC (P < 0.001) and IVC (P = 0.012) macula microvasculature compared with control group. After adjusting for risk factors (hypertension, diabetes, age and gender) SVC (P = 0.035) and IVC (P = 0.030) significantly correlated with serum uric acid. Conclusion: Serum uric acid levels are associated with microvascular changes in WMH. Fractal dimension based on OCTA imaging could help quantitatively characterize the macula microvasculature changes in WMH and may be a potential screening tool to detect serum uric acid level changes.
Keywords: Serum uric acid